1990
DOI: 10.1093/ajcn/52.4.596
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism in acute and chronic renal failure

Abstract: Energy metabolism was measured by indirect calorimetry in 86 patients with various forms of renal failure and in 24 control subjects. In patients with acute renal failure with sepsis, oxygen consumption, carbon dioxide production, and resting energy expenditure were increased (P less than 0.05). In other groups with renal failure (acute renal failure without sepsis, chronic renal failure with conservative treatment or hemodialysis, and severe untreated azotemia) these indices were not different from those of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(94 citation statements)
references
References 27 publications
6
84
0
4
Order By: Relevance
“…This finding is in accordance with some investigators (Monteon et al, 1986;Schneeweiss et al, 1990), but differs from others who found increased REE in HD patients (Ikizler et al, 1996). The exact factors affecting REE of CKD patients are not fully understood, but several mechanisms involving HD patients may lead to either increase or reduction of REE.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in accordance with some investigators (Monteon et al, 1986;Schneeweiss et al, 1990), but differs from others who found increased REE in HD patients (Ikizler et al, 1996). The exact factors affecting REE of CKD patients are not fully understood, but several mechanisms involving HD patients may lead to either increase or reduction of REE.…”
Section: Discussionsupporting
confidence: 92%
“…Os primeiros estudos que compararam o GER de pacientes com DRC na fase não dialítica e dialítica com o de indivíduos saudáveis não mostraram diferenças entre ambos os grupos 13,14 .…”
Section: Gasto Energético De Repouso Na Doença Renal Crônicaunclassified
“…Monteon et al 13 Schneeweiss et al 14 Ikizler et al 15 Avesani et al 16 O´Sullivan et al 17 Ikizler et al 24 Cuppari et al 21 Wang et al 23 Avesani et al 18 Utaka et al 22 Kamimura et al 20 Kamimura et al 5 12 …”
Section: Gasto Energético De Repouso Na Doença Renal Crônicamentioning
confidence: 99%
“…The initial research debunking the idea that those with AKI required energy intakes as high as 50 kcal/kg was done nearly 20 years ago [12,13]. Soop et al [13] reported an energy expenditure (EE) that was 128% of the basal energy expenditure (BEE) in patients with MOF and AKI requiring RRT.…”
Section: Energy/proteinmentioning
confidence: 99%